Model Pengembangan Agribisnis Ubi Kayu Untuk Mendukung Peningkatan Pendapatan Petani Di Kecamatan Pancur Batu Kabupaten Deli Serdang - Hotden L Nainggolan; Elisabeth Sri Pujiastuti (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2019)
This research aims to; a) identify the development of production and analyze the constraints on the development of cassava commodities in Pancur Batu District; b) discover the model of cassava agribusiness development in Pancur Batu District. The analytical methods used were descriptive qualitative method using SWOT matrix and quantitative descriptive analysis. The results of the study show; a) The cassava marketing channel in this area is still simple, dominated by the role of agents from farmers/ producers to industries/ processing factories; b) Capital access is a major obstacle to the development of agribusiness, as 80% of respondents said; c) The production price at the low producer/ farmer level is a barrier to the development of agribusiness, which was delivered by 78% of respondents; d) 78% of respondents expressed market access and the development of business partners was a constraint in the development of cassava agribusiness; e) Availability of land is the main strength of farmers in the development of cassava agribusiness in this region as conveyed by 83% of respondents. And 75% of respondents said that the availability of labor was not enough to support the development of agribusiness in this region, in addition to the fact that human resources were available in untrained conditions. Based on the conclusion it can be suggested that the Deli Serdang Regency Government; a) conducting training and counseling to farmers, especially in the utilization of production factors to increase their farming production; b) provide market information for farmers which includes output prices and input prices including market access for farmers; c) guarantee capital access for farmers sourced from government or private financial institutions with affordable interest rates; d) create policies to ensure the stability of production prices at the producer/ farmer level; e) bridging farmers to gain market access and development of business partners.